2012
DOI: 10.1057/jibs.2011.58
|View full text |Cite
|
Sign up to set email alerts
|

Individualism–collectivism as a moderator of the work demands–strains relationship: A cross-level and cross-national examination

Abstract: Surveying 6509 managers from 24 countries/geopolitical entities, we tested the process through which individualism-collectivism at the country level relates to employees' appraisals of and reactions to three types of work demands (i.e., work hours, workload, and organizational constraints). Our multilevel modeling results suggested that, while working the same number of hours, employees from individualistic countries reported a higher perceived workload than their counterparts in collectivistic countries. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 80 publications
6
88
1
3
Order By: Relevance
“…Yang et al (2012) emphasized the role of cultural values (i.e., individualism-collecdvism) in understanding occupational stress process. Our study found that Hong Kong health care employees and teachers in coUecdvisdc culture, like employees in Westem individualistic cultures, can also benefit from intervendon on reducing bumout and enhancing work well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al (2012) emphasized the role of cultural values (i.e., individualism-collecdvism) in understanding occupational stress process. Our study found that Hong Kong health care employees and teachers in coUecdvisdc culture, like employees in Westem individualistic cultures, can also benefit from intervendon on reducing bumout and enhancing work well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Before the analysis, we predicted that the relation between fatigue and OC may be stronger in more advanced areas as people are more individualistic and acquisitive requiring the balance of work and life. Actually, recent empirical cross-country research shows that employees from individualistic countries reported a higher perceived workload and higher turnover intentions than their counterparts in collectivistic countries while working the same number of hours (Yang et al, 2012). However, we could have considered differently, i.e., the relation might be stronger in less developed areas as laborers were less accustomed to the way of working in modern industries due to shorter period of industrialization and accordingly might be more sensitive to the stress which occurs in the process of adaptation to regularity and discipline (Kerr et al, 1960).…”
Section: Discussion and Implications For Theory And Practicementioning
confidence: 99%
“…On the other hand, 'others' normally work for substituting and may bear up under heavy workload. Actually, empirical cross-country research shows that employees from individualistic countries reported a higher perceived workload and higher turnover intentions than their counterparts in collectivistic countries while working the same number of hours (Yang, et al, 2012). This leads us to the following hypothesis:…”
Section: The Level Of Education and Comparative Importance Of Rewardsmentioning
confidence: 98%